IMPLEMENTATION OF DIPOLE ANTENNA WITH SQUARE REFLECTOR - Azhar, Muhammad Reynaldi; Suryadi, Dedy; Imansyah, Fitri (Faculty of Engineering, Universitas Tanjungpura, 2023)
This research is about how to develop a signal receiving antenna by using a tin can as a reflector and a ½ Lambda Dipole-shaped copper wire as a driver. With a direct experimental method to the research location which is useful for analyzing each signal strength captured. One of the objectives of this research is to support the improvement of the creative economy in Sungai Kupah Village, which still has inadequate signal quality. The results of this study indicate that only by using a tin can antenna can improve the quality of GSM signals. There are 2 providers used, namely Tri and Telkomsel by taking variable values of Signal Strength, RSSI, SINR, RSRP, RSRQ and taking daily data for 5 days of research in the morning and evening which aims to analyze what changes in value there are. variable data. The average value obtained by Provider Telkomsel for 5 days in the morning is Signal Strength -108.8 dBm, RSSI -78.62 dBm, SINR 3.78 dB, RSRP -108.8 dBm, RSRQ -12.1 dB, Ping 103.83 ms, Upload 60.21 Mbps, Download 9.92 Mbps. The average value obtained by Telkomsel Provider for 5 days afternoon is Signal Strength -116 dBm, RSSI -85.74 dBm, SINR 1.8 dB, RSRP -116 dBm, RSRQ -11.3 dB, Ping 156.33 ms, Upload 78.84 Mbps, Download 11.64Mbps. The average value obtained by Provider Tri for 5 days in the morning is Signal Strength -112.2 dBm, RSSI -85.42 dBm, SINR 5.88 dB, RSRP -122.2 dBm, RSRQ -9.3 dB, Ping 130.94 ms, Upload 50.84 Mbps, Download 8, 05Mbps. The average value obtained by Provider Tri for 5 days afternoon is Signal Strength -111.2 dBm, RSSI -84.34 dBm, SINR 6.62 dB, RSRP -111.2 dBm, RSRQ 9.9 dB, Ping 91.94 ms, Upload 14.60 Mbps.